2008
DOI: 10.1093/nar/gkn268
|View full text |Cite
|
Sign up to set email alerts
|

TRE-dependent transcription activation by JDP2-CHOP10 association

Abstract: The c-Jun dimerization protein 2, JDP2, is a member of the activating protein 1 (AP-1) family of transcription factors. Overexpression of JDP2 has been shown to result in repression of AP-1-dependent transcription and inhibition of cellular transformation. Other studies suggested that JDP2 may function as an oncogene. Here we describe the identification of CHOP10, a member of the CCAAT enhancer binding proteins, as a protein associating with JDP2. In contrast to the inhibition of transcription by JDP2, JDP2–CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 40 publications
1
44
1
Order By: Relevance
“…ATF3 typically dampens the response by functioning as a negative regulator and repressing transcription. However, ATF3 may act as an activator in different cellular contexts [36] and through the association with different protein partners [23]. We used a PE infusion model aiming to mimic chronic pressure overload [7,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATF3 typically dampens the response by functioning as a negative regulator and repressing transcription. However, ATF3 may act as an activator in different cellular contexts [36] and through the association with different protein partners [23]. We used a PE infusion model aiming to mimic chronic pressure overload [7,32].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, JDP2 is constitutively expressed in all cells tested [17]. JDP2 and ATF3 are able to associate with numerous bZIP protein family members and either inhibit transcription [17,[20][21][22] or potentiate transcription depending on their interacting partner [23]. Importantly, ATF3 expression is highly induced specifically in cardiomyocytes following acute challenge with isoproterenol, PE and angiotensin II [24].…”
Section: Introductionmentioning
confidence: 98%
“…We speculate that the affinity between the repressor and those promoters might vary. Aronheim's group (26) recently demonstrated that JDP2 activates transcription from TPA responsive element-dependent promoters through association with CHOP10, suggesting that JDP2 can be a transcriptional activator, as well, depending on the context. One possible hypothesis is that the CMV promoter might be regulated both positively and negatively by JDP2, and JDP2 knockdown act in both ways, whereas exogenous overexpression causes emphatic effects on the negative side.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that JDP2 recruits histone deacetylase 3 (HDAC3) to the promoters of target genes and inhibits histone acetyltransferase activity, thereby suppressing transcriptional activity (14,24). Depending on the context and cell type, however, it can alternatively act as a transcriptional activator (25,26).…”
mentioning
confidence: 99%
“…GABBR1 immunofluorescence was determined by standard techniques using an anti-GABBR1 antibody (Novus Biologicals, Littletown). Western blot for the transcription factor HoxD10 was performed on nuclear protein extract as previously described 36, 37 . RNA was extracted from PVN micro punches or cultured cells as described in the data supplement.…”
Section: Methodsmentioning
confidence: 99%